Use of non-invasive transcutaneous auricular vagus nerve stimulation: neurodevelopmental and sensory follow-up - Aljuhani, Turki; Coker-Bolt, Patricia; Katikaneni, Lakshmi; Ramakrishnan, Viswanathan; Brennan, Alyssa; George, Mark S.; Badran, Bashar W.; Jenkins, Dorothea (Frontiers in Human Neuroscience, 2023)
Objective: To assess the impact of non-invasive transcutaneous auricular vagal nerve stimulation (taVNS) paired with oral feeding on long-term neurodevelopmental and sensory outcomes. Method: We tested 21 of 35 children who as infants were gastrostomy tube (G-tube) candidates and participated in the novel, open-label trial of taVNS paired with oral feeding. To evaluate possible effects on development at 18-months after infant taVNS, we performed the Bayley-III (n=10) and Sensory Profile (SP-2, n=12) assessments before the COVID pandemic, and Cognitive Adaptive Test (CAT), Clinical Linguistics and Auditory Milestone (CLAMS), Ages and Stages Questionnaire (ASQ), and Peabody Developmental Motor Scales-2 gross motor tests as possible during and after the pandemic. We compared outcomes for infants who attained full oral feeds during taVNS ('responders') or received G-tubes ('non-responders').Results: At a mean of 19-months, taVNS 'responders' showed significantly better general sensory processing on the SP-2 than 'non-responders'. There were no differences in other test scores, which were similar to published outcomes for infants who required G-tubes. This is a provisional file, not the final typeset article Conclusion: This is the first report of neurodevelopmental follow-up in infants who received taVNSpaired feeding. They had similar developmental outcomes as historical control infants failing oral feeds who received G-tubes. Our data suggests that infants who attained full oral feeds had better sensory processing.